2016
DOI: 10.1017/etds.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Automorphisms of blowups of threefolds being Fano or having Picard number 1

Abstract: Abstract. Let X 0 be a smooth projective threefold which is Fano or which has Picard number 1. Let π : X → X 0 be a finite composition of blowups along smooth centers. We show that for "almost all" of such X, if f ∈ Aut(X) then its first and second dynamical degrees are the same. We also construct many examples of finite blowups X → X 0 , on which any automorphism is of zero entropy.The main idea is that because of the log-concavity of dynamical systems and the invariance of Chern classes under holomorphic aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Further biochemical and cellular studies in our laboratory demonstrated that S-sulfenylation of this site augments EGFR tyrosine kinase activity, thus creating a positive feedback loop with the enzymatic source of EGF-induced generation of H 2 O 2 and NADPH oxidase (Nox). 6,74 In another example, we demonstrated that S-sulfenylation of SIRT6 Cys18 leads to intermolecular disulfide formation with the transcription factor, HIF1A, disclosing a new mechanism for regulating the expression of multiple glycolytic genes. 69 A recent study of Ssulfenylation with BTD in Arabidopsis thaliana mapped more than 1000 protein targets including AtMAPK4, an orthologue to human MAPK1, which is a known redox switch.…”
Section: Profiling Protein Sulfenic Acids (─Soh)mentioning
confidence: 93%
“…Further biochemical and cellular studies in our laboratory demonstrated that S-sulfenylation of this site augments EGFR tyrosine kinase activity, thus creating a positive feedback loop with the enzymatic source of EGF-induced generation of H 2 O 2 and NADPH oxidase (Nox). 6,74 In another example, we demonstrated that S-sulfenylation of SIRT6 Cys18 leads to intermolecular disulfide formation with the transcription factor, HIF1A, disclosing a new mechanism for regulating the expression of multiple glycolytic genes. 69 A recent study of Ssulfenylation with BTD in Arabidopsis thaliana mapped more than 1000 protein targets including AtMAPK4, an orthologue to human MAPK1, which is a known redox switch.…”
Section: Profiling Protein Sulfenic Acids (─Soh)mentioning
confidence: 93%
“…The next step is to translate the condition of positive entropy into a form that can be used to give geometric conclusions. The starting point is an observation of Truong [27]: there is (perhaps after replacing φ with φ −1 ) a dominant eigenvector D of the pull-back φ * : N 1 (X) → N 1 (X), such that D is a nef divisor with D 2 = 0. We will exploit the properties of this divisor to control the intersections φ m (E) ∩ φ n (E) and ultimately show that φ is imprimitive.…”
Section: Step 2: Numerical Consequences Of Positive Entropymentioning
confidence: 99%
“…Question 1 (Bedford, cf. [27]). Does there exist a smooth blow-up of P 3 admitting a positive entropy automorphism?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this note is to give a negative answer to the following question raised by Oguiso and Truong (see [Ogu15][Question 5.11] and [Tru15][Question 2]).…”
Section: Introductionmentioning
confidence: 99%